Lack of Detection of Xenotropic Murine Leukemia Virus-Related Virus in HIV-1 Lymphoma Patients - Krista A. Delviks-Frankenberry; Chawaree Chaipan; Rachel Bagni; Kathleen Wyvill; Robert Yarchoan; Vinay K. Pathak (Advances in Virology)
Xenotropic murine leukemia virus-related virus (XMRV) is a gammaretrovirus reported to be associated with human prostate cancer and chronic fatigue syndrome. Since retroviruses cause various cancers, and XMRV replication might be facilitated by HIV-1 co-infection, we asked whether certain patients with HIV-associated lymphomas are infected with XMRV. Analysis of PMBCs and plasma from 26 patients failed to detect XMRV by PCR, ELISA, or Western blot, suggesting a lack of association between XMRV and AIDS-associated lymphomas.